2014
DOI: 10.1063/1.4874840
|View full text |Cite
|
Sign up to set email alerts
|

Polarity-inverted ScAlN film growth by ion beam irradiation and application to overtone acoustic wave (000-1)/(0001) film resonators

Abstract: Polarity inversion in wurtzite film is generally achieved by the epitaxial growth on a specific under-layer. We demonstrate polarity inversion of c-axis oriented ScAlN films by substrate ion beam irradiation without using buffer layer. Substrate ion beam irradiation was induced by either sputtering a small amount of oxide (as a negative ion source) onto the cathode or by applying a RF bias to the substrate. Polarity of the films was determined by a press test and nonlinear dielectric measurement. Second overto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 27 publications
(26 reference statements)
1
24
0
Order By: Relevance
“…4 More recently, these studies have been extended to the polarization inverted resonators 9 and YbGaN resonators. 10 Recent Sc x Al (1Àx) N resonator studies 5,6 have focused on the low Sc concentration region (x < 0.15), probably either because the acoustic wave attenuation loss (1/Q factor) in high Sc concentration films was expected to be too large for use as practical resonators or because it is difficult to realize a highly oriented film in the high Sc concentration region, despite the fact that electromechanical coupling has been demonstrated to be proportional to the Sc concentration. However, GHz surface acoustic wave filters with high Q value of 660 were recently reported in a high Sc concentration film on a SiC substrate structure.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…4 More recently, these studies have been extended to the polarization inverted resonators 9 and YbGaN resonators. 10 Recent Sc x Al (1Àx) N resonator studies 5,6 have focused on the low Sc concentration region (x < 0.15), probably either because the acoustic wave attenuation loss (1/Q factor) in high Sc concentration films was expected to be too large for use as practical resonators or because it is difficult to realize a highly oriented film in the high Sc concentration region, despite the fact that electromechanical coupling has been demonstrated to be proportional to the Sc concentration. However, GHz surface acoustic wave filters with high Q value of 660 were recently reported in a high Sc concentration film on a SiC substrate structure.…”
mentioning
confidence: 97%
“…High Sc concentration ScAl alloys are difficult to synthesize, and a number of alloy targets for each Sc concentration are required in the experiments. Sc metal targets are easily oxidized in air, 10 and furthermore, pre-sputtering cleaning of the target surface is ineffective for overcoming this problem because the oxygen penetrates beyond the surface of the target. Sc ingot sputtering deposition makes it possible to use fresh and high purity Sc metal for each deposition.…”
mentioning
confidence: 99%
“…SEM-EDX measurements indicated an increased oxygen level of more than 5% in this sample. It could, therefore, be suggested that due to the high oxygen affinity of the Sc-target, 12 an increase of its contribution to Al 1−x Sc x N leads to an oxygen induced early transition away from piezoelectric wurzite Al 1−x Sc x N. While it is prudent to assume the new phase is cubic Al 1−x Sc x N, 10 no traces of it could be observed in the XRD diffraction patterns. Before this breakdown of polar orientation, however, the crystallites prove to be well aligned, as can be concluded from the narrow full width at half maximum (FWHM) of (0002)-reflection rocking curves.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Enhancements of more than 400% have been measured for the longitudinal and transversal response to stress, d 33 and d 31 , respectively. 15 The underlying reason for this profound change in properties is understood to be the presence of a metastable hexagonal phase in ScN.…”
mentioning
confidence: 99%
“…This property is used in a wide range of microelectromechanical systems (MEMS), e.g., sensors, actuators, and energy harvesters to power micro-sized devices [6][7][8][9][10]. …”
Section: Piezoelectric Coatingsmentioning
confidence: 99%